2009
DOI: 10.1007/s00415-009-5405-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype genotype analysis in 15 patients presenting a congenital myasthenic syndrome due to mutations in DOK7

Abstract: Congenital myasthenic syndromes (CMSs) are a heterogeneous group of diseases caused by genetic defects affecting neuromuscular transmission. Mutations of DOK7 have recently been described in recessive forms of CMS. Dok-7 is a cytoplasmic post-synaptic protein co-activator of the muscle-specific receptor-tyrosine kinase (MuSK) involved in neuromuscular synaptogenesis and maintenance. We report clinical, morphological and molecular data on 15 patients with mutations in DOK7. Eleven different mutations (5 novel) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 23 publications
4
62
0
2
Order By: Relevance
“…Numerous mutations have been identified in DOK7 Muller et al, 2007;Anderson et al, 2008;Selcen et al, 2008;Vogt et al, 2009;Ben Ammar et al, 2010). Nearly all patients carry a common 1124_1127dupTGCC mutation in exon 7.…”
Section: Endplate Achr Deficiency Due To Defects In Dok-7mentioning
confidence: 99%
“…Numerous mutations have been identified in DOK7 Muller et al, 2007;Anderson et al, 2008;Selcen et al, 2008;Vogt et al, 2009;Ben Ammar et al, 2010). Nearly all patients carry a common 1124_1127dupTGCC mutation in exon 7.…”
Section: Endplate Achr Deficiency Due To Defects In Dok-7mentioning
confidence: 99%
“…In 2006, mutations in the DOK7 gene were identified to cause a form of CMS with limb-girdle weakness where patients do not benefit from pyridostigmine treatment [4]. Subsequently, detailed clinical analysis of DOK7 patients revealed that many of them show external eye muscle involvement (often ptosis, less frequent ophthalmoplegia) contrary to the original concept of pure limb girdle weakness [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 96%
“…Généralement bien tolérés, ils permettent une diminution au moins partielle des symptômes dans les SMC post-synaptiques mais peuvent nécessiter une association à d'autres traitements [1]. Ils risquent d'aggraver les SMC par déficits en AchE, les syndromes du canal lent et les déficits en Dok-7 [2]. Dans ces cas, leur utilisation prudente doit être réservée aux patients qui ne tolèrent pas les autres thérapeutiques.…”
Section: Discussionunclassified
“…Comme dans notre observation, la 3,4 DAP a permis une progression thérapeutique efficace et parfaitement tolérée. Cependant, comme pour la pyridostigmine, son administration doit être prudente dans les SMC par déficit en Dok-7 [2]. L'utilisation de la 3,4 DAP dans les syndromes pré-synaptiques serait intéressante mais ceci reste à confirmer [5].…”
Section: Discussionunclassified